First report of hovering guard bees of the Paleotropical stingless bee Tetrigona apicalis (Hymenoptera: Apidae: Meliponini) - Michael Burgett (2020)
© 2019, INRA, DIB and Springer-Verlag France SAS, part of Springer Nature. For eusocial bees, colony defense is paramount. An uncommon strategy is the deployment of hovering guard bees, which has been previously described for only a few species of Neotropical meliponines. This report describes the use of flying guards for the Paleotropical stingless bee species Tetrigona apicalis (Smith) which is the first known species in the region to incorporate this defense strategy. The first appearance of hovering guards occurs ca. 0800, and the number of guards increases until an assemblage of ca. several to 25 guards is formed within an hour of the first appearance of a flying guard. The cloud of hovering guards remains throughout the day until dusk and has a continuous presence unless interrupted by rain. The group hovers in front of the entrance tube out to a distance of 10 to 35 cm with the guards facing the entrance tube. The length of time an individual hovering guard bee spends in flight averaged 17 min 52 s ± 18 min 2 s. The longest hovering flight was 1 h 48 min 46 s. This compares to a reported guard flight time of ca. 58 min for the Neotropical meliponine Tetragonisca angustula, the only other stingless bee species where flying guard flight times have been investigated.